Functional recovery of a 41-year-old quadriplegic spinal cord injury patient following multiple intravenous infusions of autologous adipose-derived mesenchymal stem cells: a case report - Vij, Ridhima; Kim, Hosu; Park, Hyeonggeun; Cheng, Thanh; Lotfi, Djamchid; Chang, Donna (Frontiers in Transplantation, 2023)
Spinal cord injury (SCI) is a debilitating disease with clinical manifestations ranging from incomplete neurological deficits affecting sensory and motor functions to complete paralysis. Recent advancements in stem cell research have elucidated the therapeutic potential of mesenchymal stem cells (MSCs) for the treatment of patients with SCI. Here, we present a case of a 41-year-old quadriplegic male individual who experienced a traumatic C-5 incomplete SCI, after slipping off a boat in Florida Keys on August 4, 2017. He was diagnosed with C5-C6 Grade 2 anterolisthesis with flexion teardrop fracture of the anterior C6 with jumped facet on the right and perched facet on the left at C5-C6 with spinal canal stenosis. On September 12, 2019, an Individual Expanded Access Protocol was approved for administration of multiple infusions of autologous, adipose-derived MSCs (adMSCs) for the treatment of this quadriplegic incomplete C5-6 SCI patient. Thirty-four (34) recurrent infusions each with 200 million cells were administered, over a period of ~ 2.5 years, which resulted in significant improvements in his quality-of-life as demonstrated by substantial improvements in SCIM-III (Spinal Cord Independence Measure III) scores. Additionally, electromyography/nerve conduction velocity (EMG/NCV) studies showed improvements in the patient's motor and sensory function. No safety concerns were presented, and no serious adverse events were reported during the entire course of treatment. Multiple intravenous infusions of autologous HB-adMSCs for treatment of SCI demonstrated significant enhancements in the patient's neurological function with improved quality-of-life. Further research is needed to evaluate the results of this study.